2022
DOI: 10.1136/bmjopen-2021-051466
|View full text |Cite
|
Sign up to set email alerts
|

Automatic vein measurement by ultrasonography to prevent peripheral intravenous catheter failure for clinical practice using artificial intelligence: development and evaluation study of an automatic detection method based on deep learning

Abstract: ObjectivesComplications due to peripheral intravenous catheters (PIVC) can be assessed using ultrasound imaging; however, it is not routinely conducted due to the need for training in image reading techniques. This study aimed to develop and validate a system that automatically measures blood vessel diameters on ultrasound images using artificial intelligence (AI) and provide recommendations for selecting an implantation site.DesignPilot study.SettingThe University of Tokyo Hospital, Japan.Primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…One study reported a remotely supervised ultrasound training program 32. Other USG PIVC training strategies featured in the literature that hold promise include artificial intelligence vessel image interpretation,42 immersive virtual reality,43 peer-assisted learning,44 and clinician rotations to the hospital vascular access team 45…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a remotely supervised ultrasound training program 32. Other USG PIVC training strategies featured in the literature that hold promise include artificial intelligence vessel image interpretation,42 immersive virtual reality,43 peer-assisted learning,44 and clinician rotations to the hospital vascular access team 45…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a remotely supervised ultrasound training program. 32 Other USG PIVC training strategies featured in the literature that hold promise include artificial intelligence vessel image interpretation, 42 immersive virtual reality, 43 peer-assisted learning, 44 and clinician rotations to the hospital vascular access team. 45 Achieving competence with USG PIVC insertion is an area that needs more research, particularly as the studies in this review reported a wide range of successful cannulations needed for minimal competency.…”
Section: Education Strategies and Competencementioning
confidence: 99%
“…Recently, POCUS educational programs have been developed for nurses [31][32][33], and US training on the transgluteal cleft approach will need to be developed and disseminated because it is already presented in expert consensus documents and guidelines to assess constipation [14,28]. In addition, the development of artificial intelligence (AI)-assisted functions would be an effective means of making the procedure easier for nurses, as has already been put to practical use in the observation of the bladder and rectum in transabdominal approaches [25,34], peripheral veins [35], etc.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] We previously reported the application of an automated vessel detection system (AVDS) using AI to support ultrasound beginners. 17 In addition, AVDS was implemented in a commercially available smartphone ultrasound device. It detects areas in short-axis images that have the characteristics of a vessel (circular or elliptical anechoic area) and displays the vein size in the form of numbers and colors in real time (Figure 1).…”
Section: Introductionmentioning
confidence: 99%